Percepções de agricultores familiares e técnicos sobre mercado institucional no desenvolvimento da agricultura familiar no Vale do Ribeira - Gomes, Tiago Tomaz (Universidade Federal de São Carlos, 2018)
Family farming is a social and economic segment of strategic importance for the country, since it ensures an essential part of the Brazilian society's food supply. Recently a set of policies directed to the Brazilian family agriculture was constructed. Among these policies is the so-called institutional food market of family agriculture (PAA and PNAE) also applied to the Ribeira Valley region. In this context, the objective of the research is to analyze the perceptions of key actors regarding these two public policy programs, their relations with ATER and also with their social organizations. It was sought to identify, characterize and describe the main impacts resulting from access to PAA and PNAE. We adopted the qualitative approach from the comprehensive sociology, which guided the construction of the semi-structured interviews and the analysis of the material. The results show that the public policies studied have the potential to positively impact the reality of these farmers, but they present limitations on the reach of the target population (family farmers in the region of the study area), especially due to the lack of information and understanding of the operational the need for qualified technical assistance and improvement in associative and cooperative practices to obtain better results.
Perceptions of family farmers and technicians on institutional market in the development of family agriculture in the Ribeira Valley
Keywords: Políticas públicas; Desenvolvimento rural; Agroecologia; Public policies; Rural development; Agroecology; CIENCIAS AGRARIAS::AGRONOMIA::EXTENSAO RURAL